A systematic literature review on factors of language learning enjoyment among esl/efl learners - Norfadzillah Chin; Noraini Said; Vincent Pang (Human Resource Management Academic Research Society, 2024)
The study addresses a call to conduct a systematic literature review on the factors of language learning enjoyment among ESL/EFL learners, by adopting the protocol of RepOrting Standards for Systematic Evidence Syntheses (ROSES) which included three phases: searching, screening and critical appraisal and synthesis. This systematic literature review (SLR) was guided by a research question “What are the factors related to ESL/EFL language learning enjoyment” formulated using PICo, a tool to build focused research questions, using three key concepts: Population of the problem (English as a second language/ English as a foreign language learners (ESL/EFL learners), interest (Factors of Language Learning Enjoyment) and context (ESL /EFL Classroom) . 3 main databases (Scopus, ProQuest, ERIC) and 1 supporting database (Google Scholar) were explored to select the relevant articles. These articles were filtered, read and selected and finally underwent critical appraisal and synthesis by experts using Mixed Method Appraisal Tool (MMAT). The review of these articles resulted in six main themes- teacher- factor, social factor, engagement, motivation, self-attainment and autonomy. Several recommendations are suggested related to further investigate on retaining the momentum of enjoyment in classroom.